Rancang Bangun Sistem Informasi Keuangan Berbasis Website - Ginting, Rini Antika Br; Nurfaizah, Nurfaizah; Musliman, Dedy; Yasri, Zul; Rahmayani, Mentari Tri Indah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The development of information and communication technology has a significant impact, especially in the business world, including the use of financial information system. This research designs a financial information system for Toko Humairah 2 with the aim of improving the efficiency and accuracy of financial management. The System Development Life Cycle (SDLC) method is employed in the development, involving requirements analysis, the application of Unified Modeling Language (UML), and flowcharts. System testing indicates that this system simplifies financial record- keeping, enhances data accuracy, and provides easy access for users. The implementation includes menu-login, dashboard, initial balance, cash in/out, general journal, ledger, cash flow, profit and loss, and financial graphs. The system is expected to contribute positively to improving the efficiency and accuracy of the store's financial management.